Character education to improving student learning outcomes - Tjung Hauw Sin; Firunika Intan Cahyani (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
The issue of character education is one of the problems that need to be addressed in Indonesian education. In this study, researchers focused on the low implementation of the character and role of parents in improving the learning outcomes of Physical Education at middle school students. This study aims to analyze the relationship between character and learning outcomes of Physical Education at middle school students. The type of research used in this research is quantitative correlation research with a total sample of 30 students. The research instrument is a implementation character education at school. The results of the research are that there is no significant relationship between character and learning outcomes of Physical Education at Middle school students. Thus it can be seen that character values do not have an impact on improving learning outcomes in the Physical Education subject in Junior High School students, this is because the implementation of character in the physical education subject has not yet been implemented properly, so that it has an impact on student learning outcomes who are still below the limit value.